Effects of dexmedetomidine combined with dezocine on T lymphocytes, NK cells and cognitive function in elderly patients with gastrointestinal cancer after radical surgery: Effects of dexmedetomidine and dezocine on cells - Ai, Zijian (Cellular and Molecular Biology, 2023)
This study aimed to determine how dexmedetomidine and dezocine interact on T lymphocytes, NK cells and cognitive function in elderly individuals with gastrointestinal cancer after radical surgery. 104 elderly individuals with gastrointestinal cancer after radical surgery who visited our hospital from January 2020 to April 2022 were chosen. The patients were randomly divided into the Control Group (Group C) and Observation Group (Group O) with 52 cases each. Group C was anesthetized with sufentanil, while Group O was anesthetized with dexmedetomidine combined with dezocine. The changes in T lymphocytes, NK cells and their cognitive function were compared before the operation, 1 day after the operation and 3 days after the operation. In the experiment, the cognitive function of the individuals after the operation was evaluated with the Mini-Mental State Examination (MMSE). The overall comparison results indicated that among CD3+, CD4+, CD8+, and CD4+/CD8+, there were statistically significant variations in the interplay between groups over time (P<0. 05). Before anesthesia, the two categories did not vary significantly from one another in the percentage of T lymphocytes, the percentage of NK cells and the score of the MESS scale (P>0. 05). At 1 day and 3 days after the operation, the CD3+, CD4+, and CD4+/CD8+ in Group O were remarkably higher than those in Group C (P<0. 05). At 1 day and 3 days after the operation, the CD8+in Group O was significantly lower than that in Group C (P<0. 05). Overall comparison results: There was a variation that is numerically meaningful in the percentage of NK cells over time, groups and time interactions (P<0. 05). One day after surgery, there was no discernible change in the proportion of NK cells between the two groups (P>0. 05). Three days after the operation, the NK cells in Group O were higher than those in Group C, and the difference was statistically significant (P<0. 05). The scores of the MMSE scale in both groups decreased 3 days after the operation compared with those before anesthesia. However, the score of MMSE in Group O was superior to Group C 3 days after the operation, and the difference between the two groups was statistically significant (P<0. 05). The application of dexmedetomidine combined with dezocine in elderly individuals with gastrointestinal cancer after radical surgery can increase the percentage of T lymphocytes and NK cells after surgery and promote faster recovery of cognitive function.